Gestão do Conhecimento em Instituição de Ensino Pública Multicampi: proposta implantação a partir das diretorias de planejamento e administração dos campi do instituto federal do Paraná - Meireles, Belquis Oliveira (2017)
Knowledge Management [GC] has been recognized as an indispensable strategic resource for the success of organizations in today's society, based on knowledge. Although, proposing the implementation of a GC program in a multicampus public educational institution is a considerable challenge, because it requires that the specifics of this organizational model are respected and that know how the knowledge of the cycle evolves in its interaction contexts. The literature recommends that initiatives related to knowledge start with a pilot program, being more indicated that it starts from a sector or a segment of the organization. For this reason, this study aimed to propose a implementation plan of GC at the Federal Institute of Paraná [IFPR], from the Planning and Administration Directors [DPA] of their campuses. This is a single case study with a qualitative approach, implemented in two phases: a descriptive and another applied. The descriptive phase included two types of diagnoses: the first researched which the critical success factors in the evolution of knowledge cycle in the context of interaction of the directors object of study; the other, what mechanisms, the systems and GC practices or present in the DPA or required fpr these. The diagnosis of those present is relevant because it shows the resources currently used in the development of organizational knowledge cycle; on the other hand, those who are needed because they help to make the development of the GC implementation plan in the institution. At this stage, it was used as sources of information, semi-structured interviews and documents. In the process of analysis of this phase, it was used the content analysis technique, with the help of software NVivo® 11.The results of the first type of diagnosis - critical success factors - showed that the activities of DPA are permeated by different contexts of interaction in which each of them has different aspects, acting or as facilitators or as barriers to knowledge evolution cycle. Among the barriers, the lack of a standard of institutional communication, the inefficiency of the flows, the knowledge explicitation and the updating of the institutional database, and the difficulty of the Pro-Rectos in establishing suitable guidelines for the work of the DPA are alluded to.The results of the second type of diagnosis - mechanisms, systems and GC practices - showed that, although there are no structured GC practices, the organization has the potential to deploy them, because it already works with several mechanisms and GC systems that can support them. In the second phase of this study - applied it was proposed a plan for the implementation of GC in IFPR from DPA in their campuses. It was suggested also, initiatives for the elimination / reduction of barriers to GC diagnosed. And finally, it was suggested the institution of some GC practices, appropriate for the case study. This paper brings two constributions to the academic. One of them showed that in public multicampus institutions, the evolution of organizational knowledge cycle occurs in different ways in each of its interaction contexts. The other contribution is to allow the proposed deployment plan is used by other public multicampus Educational Institutions. As a contribution to the practice of IFPR has been the proposal of a GC implementation plan in which this work has already advanced some actionsKnowledge Management [GC] has been recognized as an indispensable strategic resource for the success of organizations in today's society, based on knowledge. Although, proposing the implementation of a GC program in a multicampus public educational institution is a considerable challenge, because it requires that the specifics of this organizational model are respected and that know how the knowledge of the cycle evolves in its interaction contexts. The literature recommends that initiatives related to knowledge start with a pilot program, being more indicated that it starts from a sector or a segment of the organization. For this reason, this study aimed to propose a implementation plan of GC at the Federal Institute of Paraná [IFPR], from the Planning and Administration Directors [DPA] of their campuses. This is a single case study with a qualitative approach, implemented in two phases: a descriptive and another applied. The descriptive phase included two types of diagnoses: the first researched which the critical success factors in the evolution of knowledge cycle in the context of interaction of the directors object of study; the other, what mechanisms, the systems and GC practices or present in the DPA or required fpr these. The diagnosis of those present is relevant because it shows the resources currently used in the development of organizational knowledge cycle; on the other hand, those who are needed because they help to make the development of the GC implementation plan in the institution. At this stage, it was used as sources of information, semi-structured interviews and documents. In the process of analysis of this phase, it was used the content analysis technique, with the help of software NVivo® 11.The results of the first type of diagnosis - critical success factors - showed that the activities of DPA are permeated by different contexts of interaction in which each of them has different aspects, acting or as facilitators or as barriers to knowledge evolution cycle. Among the barriers, the lack of a standard of institutional communication, the inefficiency of the flows, the knowledge explicitation and the updating of the institutional database, and the difficulty of the Pro-Rectos in establishing suitable guidelines for the work of the DPA are alluded to.The results of the second type of diagnosis - mechanisms, systems and GC practices - showed that, although there are no structured GC practices, the organization has the potential to deploy them, because it already works with several mechanisms and GC systems that can support them. In the second phase of this study - applied it was proposed a plan for the implementation of GC in IFPR from DPA in their campuses. It was suggested also, initiatives for the elimination / reduction of barriers to GC diagnosed. And finally, it was suggested the institution of some GC practices, appropriate for the case study. This paper brings two constributions to the academic. One of them showed that in public multicampus institutions, the evolution of organizational knowledge cycle occurs in different ways in each of its interaction contexts. The other contribution is to allow the proposed deployment plan is used by other public multicampus Educational Institutions. As a contribution to the practice of IFPR has been the proposal of a GC implementation plan in which this work has already advanced some actionsKnowledge Management [GC] has been recognized as an indispensable strategic resource for the success of organizations in today's society, based on knowledge. Although, proposing the implementation of a GC program in a multicampus public educational institution is a considerable challenge, because it requires that the specifics of this organizational model are respected and that know how the knowledge of the cycle evolves in its interaction contexts. The literature recommends that initiatives related to knowledge start with a pilot program, being more indicated that it starts from a sector or a segment of the organization. For this reason, this study aimed to propose a implementation plan of GC at the Federal Institute of Paraná [IFPR], from the Planning and Administration Directors [DPA] of their campuses. This is a single case study with a qualitative approach, implemented in two phases: a descriptive and another applied. The descriptive phase included two types of diagnoses: the first researched which the critical success factors in the evolution of knowledge cycle in the context of interaction of the directors object of study; the other, what mechanisms, the systems and GC practices or present in the DPA or required fpr these. The diagnosis of those present is relevant because it shows the resources currently used in the development of organizational knowledge cycle; on the other hand, those who are needed because they help to make the development of the GC implementation plan in the institution. At this stage, it was used as sources of information, semi-structured interviews and documents. In the process of analysis of this phase, it was used the content analysis technique, with the help of software NVivo® 11.The results of the first type of diagnosis - critical success factors - showed that the activities of DPA are permeated by different contexts of interaction in which each of them has different aspects, acting or as facilitators or as barriers to knowledge evolution cycle. Among the barriers, the lack of a standard of institutional communication, the inefficiency of the flows, the knowledge explicitation and the updating of the institutional database, and the difficulty of the Pro-Rectos in establishing suitable guidelines for the work of the DPA are alluded to.The results of the second type of diagnosis - mechanisms, systems and GC practices - showed that, although there are no structured GC practices, the organization has the potential to deploy them, because it already works with several mechanisms and GC systems that can support them. In the second phase of this study - applied it was proposed a plan for the implementation of GC in IFPR from DPA in their campuses. It was suggested also, initiatives for the elimination / reduction of barriers to GC diagnosed. And finally, it was suggested the institution of some GC practices, appropriate for the case study. This paper brings two constributions to the academic. One of them showed that in public multicampus institutions, the evolution of organizational knowledge cycle occurs in different ways in each of its interaction contexts. The other contribution is to allow the proposed deployment plan is used by other public multicampus Educational Institutions. As a contribution to the practice of IFPR has been the proposal of a GC implementation plan in which this work has already advanced some actionsKnowledge Management [GC] has been recognized as an indispensable strategic resource for the success of organizations in today's society, based on knowledge. Although, proposing the implementation of a GC program in a multicampus public educational institution is a considerable challenge, because it requires that the specifics of this organizational model are respected and that know how the knowledge of the cycle evolves in its interaction contexts. The literature recommends that initiatives related to knowledge start with a pilot program, being more indicated that it starts from a sector or a segment of the organization. For this reason, this study aimed to propose a implementation plan of GC at the Federal Institute of Paraná [IFPR], from the Planning and Administration Directors [DPA] of their campuses. This is a single case study with a qualitative approach, implemented in two phases: a descriptive and another applied. The descriptive phase included two types of diagnoses: the first researched which the critical success factors in the evolution of knowledge cycle in the context of interaction of the directors object of study; the other, what mechanisms, the systems and GC practices or present in the DPA or required fpr these. The diagnosis of those present is relevant because it shows the resources currently used in the development of organizational knowledge cycle; on the other hand, those who are needed because they help to make the development of the GC implementation plan in the institution. At this stage, it was used as sources of information, semi-structured interviews and documents. In the process of analysis of this phase, it was used the content analysis technique, with the help of software NVivo® 11.The results of the first type of diagnosis - critical success factors - showed that the activities of DPA are permeated by different contexts of interaction in which each of them has different aspects, acting or as facilitators or as barriers to knowledge evolution cycle. Among the barriers, the lack of a standard of institutional communication, the inefficiency of the flows, the knowledge explicitation and the updating of the institutional database, and the difficulty of the Pro-Rectos in establishing suitable guidelines for the work of the DPA are alluded to.The results of the second type of diagnosis - mechanisms, systems and GC practices - showed that, although there are no structured GC practices, the organization has the potential to deploy them, because it already works with several mechanisms and GC systems that can support them. In the second phase of this study - applied it was proposed a plan for the implementation of GC in IFPR from DPA in their campuses. It was suggested also, initiatives for the elimination / reduction of barriers to GC diagnosed. And finally, it was suggested the institution of some GC practices, appropriate for the case study. This paper brings two constributions to the academic. One of them showed that in public multicampus institutions, the evolution of organizational knowledge cycle occurs in different ways in each of its interaction contexts. The other contribution is to allow the proposed deployment plan is used by other public multicampus Educational Institutions. As a contribution to the practice of IFPR has been the proposal of a GC implementation plan in which this work has already advanced some actionsKnowledge Management [GC] has been recognized as an indispensable strategic resource for the success of organizations in today's society, based on knowledge. Although, proposing the implementation of a GC program in a multicampus public educational institution is a considerable challenge, because it requires that the specifics of this organizational model are respected and that know how the knowledge of the cycle evolves in its interaction contexts. The literature recommends that initiatives related to knowledge start with a pilot program, being more indicated that it starts from a sector or a segment of the organization. For this reason, this study aimed to propose a implementation plan of GC at the Federal Institute of Paraná [IFPR], from the Planning and Administration Directors [DPA] of their campuses. This is a single case study with a qualitative approach, implemented in two phases: a descriptive and another applied. The descriptive phase included two types of diagnoses: the first researched which the critical success factors in the evolution of knowledge cycle in the context of interaction of the directors object of study; the other, what mechanisms, the systems and GC practices or present in the DPA or required fpr these. The diagnosis of those present is relevant because it shows the resources currently used in the development of organizational knowledge cycle; on the other hand, those who are needed because they help to make the development of the GC implementation plan in the institution. At this stage, it was used as sources of information, semi-structured interviews and documents. In the process of analysis of this phase, it was used the content analysis technique, with the help of software NVivo® 11.The results of the first type of diagnosis - critical success factors - showed that the activities of DPA are permeated by different contexts of interaction in which each of them has different aspects, acting or as facilitators or as barriers to knowledge evolution cycle. Among the barriers, the lack of a standard of institutional communication, the inefficiency of the flows, the knowledge explicitation and the updating of the institutional database, and the difficulty of the Pro-Rectos in establishing suitable guidelines for the work of the DPA are alluded to.The results of the second type of diagnosis - mechanisms, systems and GC practices - showed that, although there are no structured GC practices, the organization has the potential to deploy them, because it already works with several mechanisms and GC systems that can support them. In the second phase of this study - applied it was proposed a plan for the implementation of GC in IFPR from DPA in their campuses. It was suggested also, initiatives for the elimination / reduction of barriers to GC diagnosed. And finally, it was suggested the institution of some GC practices, appropriate for the case study. This paper brings two constributions to the academic. One of them showed that in public multicampus institutions, the evolution of organizational knowledge cycle occurs in different ways in each of its interaction contexts. The other contribution is to allow the proposed deployment plan is used by other public multicampus Educational Institutions. As a contribution to the practice of IFPR has been the proposal of a GC implementation plan in which this work has already advanced some actions